Unraveling the legal and regulatory framework for investment in Ethiopia : an in-depth gap exploration and analysis - Kabre, Rimdolmsom Jonathan (University of Pretoria, 2023)
Dissertation (LLM ((International Trade and Investment Law in Africa))--University of Pretoria, 2023.